Canagliflozin for weight loss in non-diabetic individuals - Tousif, Meirajuddin; Akhtar, Maria; Oza, Yugam (International Journal of Research in Medical Sciences, 2023)
Canagliflozin, a sodium-glucose co-transporter 2 (SGLT2) inhibitor, is primarily used as an anti-diabetic medication, but recent evidence suggests its potential role in promoting weight loss in individuals without diabetes. A comprehensive literature review was conducted, analysing relevant studies published between 2013-2021, focusing on the efficacy and safety of canagliflozin for weight loss in non-diabetic populations. Four relevant studies were identified, which consistently demonstrated that canagliflozin treatment in non-diabetic individuals resulted in significant weight loss compared to placebo or other comparators. The weight loss effect of canagliflozin appears to be mediated by increased urinary glucose excretion, caloric loss, and reduction in body fat mass. Canagliflozin also showed improvements in cardiometabolic risk factors, such as blood pressure and lipid profiles. This review, therefore, provides substantial evidence supporting the potential use of canagliflozin as an effective treatment for weight loss in non-diabetic individuals, suggesting it could be a valuable therapeutic option for addressing the rising prevalence of obesity and associated comorbidities. However, further well-designed clinical trials are needed to elucidate the optimal dosing, long-term safety, and potential side effects of canagliflozin in this specific population.